Analise multidimensional dos indicadores de rendimento desportivo de equipas profissionais de Futebol - Belli, R.; Dias, G.; Gama, J.; Couceiro, M.Vaz, V. (Revista Portuguesa de Ciências do Desporto, 2015)
The main objective of this study was to investigate the multi-dimensional sports performance indicators in professional football teams. We used three different methods: (1) categorization of the type of offensive game actions; (2) probability of interaction between players and (3) centroid player. We analyzed two matches and observed 517 offensive collective actions and 571 intra-team interactions. The results indicate a higher probability of interaction from the following players: central defender, right defender and goalkeeper. The data also show that Type II collective actions (i.e., starting and running) occurred more frequently, without any possibility of immediate termination. The analysis of the player centroid indicates that player 6 (defensive midfielder) was the one who had the best overall rating regarding the number of interactions performed during the first game (G_6=0.5954). In the second game, the results show that player 10 (midfielder) had the higher ranking regarding the number of interactions performed (g_10=0.6057). We concluded that the multidimensional analysis implemented in this study allowed us to follow the sport performance indicators related with the collective performance. This method provides relevant information to the coach about the self-organization processes in field-invasion team sports.